Mechanical and Hydraulic Properties of Recycled Concrete Aggregates Mixed with Clay Brick Aggregates and Particle Breakage Characteristics for Unbound Road Base and Subbase Materials in Vietnam - Trong Lam Nguyen (Sustainability, 2022)
The construction industry is one of the key industries with high potential for the circular economy; the promotion of reuse and recycling of construction and demolition waste (CDW) is essential for sustainable urban development. In this study, a series of compaction, California bearing ratio, saturated hydraulic conductivity, and particle breakage tests of well– and poor–graded mixtures of recycled clay brick aggregates (RCBs) and recycled concrete aggregates (RCAs) with maximum aggregate diameters of 19, 25, and 37.5 mm were carried out to examine the practical application of those mixtures to unbound roadbed materials in Vietnam. The experimental results suggest that the maximum amount of RCBs added to RCAs should be less than 30% when applied to unbound roadbed materials. In addition, it was found that the mixing proportions of RCBs and RCAs and the maximum aggregate diameter, gradation of aggregates, and initial moisture condition control the saturated hydraulic conductivity. Further, the particle breakage characteristics under compaction were carefully examined, and it was found that the percentage increment/decrement, as well as a newly introduced method of estimating the mixing proportions of RCAs and RCBs in the fine fraction (<2.36 mm), is effective in understanding the mechanism of particle breakage of RCA and RCB mixtures.